Description of Adolescents' Knowledge and Attitudes Regarding Sexual Harassment - Dynda Tri Azrina; Masrina Munawarah Tampubolon; Wasisto Utomo (Journal of Education Technology Information Social Sciences and Health, 2024)
Introduction: Sexual harassment can occur anywhere, anytime, and to anyone, including adolescents, therefore knowladge is needed as a self-protection effort against cases of sexual harassment. The aim of this research is to description of adolescents knowledge and attitudes about sexual harassment. Method: This study is quantitative research with a descriptive design. The sample for this research is 265 respondents from grade XI of SMAN 10 Pekanbaru and SMAN 14 Pekanbaru, selected using a cluster random sampling technique. Data analysis in this study used univariate. Results: The description of adolescents’ knowledge about sexual harassment is good, especially regarding the meaning (94,7%), forms (95,5%), impacts (97,7%), and efforts to prevent sexual harassment (75,5%). The description of adolescents' attitudes towards sexual harassment is positive (53.6%). Conclusion: The majority of adolescents have good knowledge and positive attitudes.